COMPARATIVE STUDY BETWEEN JODOFORM-VASELINE NASAL PACKING AND MEROCEL HEMOX 10 cm AFTER THE SEPTO-TURBINOPLASTY OR RHINOSEPTOPLASTY PROCEDURE - Marolov, Marjan; Kopacheva Barsova, Gabriela; Dokoska, Marija (European Rhinologic Society, 2019)
Background: The purpose of our study was to compare Merocel (Merocel Hemox 10 cm) and Jodoform-Vaseline cotton tampons (JVT) after a rhinoseptoplasty procedure in efficiency and patient comfort. Methods: We carried out a prospective study of 53 patients who had undergone surgery between 01/2018 and 01/2019. GroupA, packed with Merocel was composed of 29 patients, and GroupB packed with JVT was composed of 24 patients. A standard scale ranging from zero (no symptoms) to 5 (most severe symptoms) was used to assess subjective symptoms. To compare the usefulness of materials we evaluated the after-surgery bleeding and bleeding after nasal pack removing, discomfort of the patient at 12h and after 72h, discomfort during removing nasal pack. Secretions and crusts were evaluated 1 week and 2 weeks after surgery in both groups. Results: A total of 53 patients were enrolled in the study, 37 women and 16 men; age range 15-42 with a mean age of 34 years. After removing of the nasal pack in the GroupA, in 27 cases no bleeding was present, and in 2 cases there was present bleeding. In the GroupB in 19 cases no bleeding was present, and in 5 cases there was present bleeding. In the GroupA overall average discomfort score was 2, and in the GroupB overall average discomfort was 3. We noticed statistically significance reduction of nasal secretions and crusts at 1 week after surgery. The difference is not statistically significant 2 weeks after surgery. Difference in discomfort related to nasal packing is statistically significant (p < 0.05) regarding the pain during packing removal, the general satisfaction and the pressure. Conclusions: Merocel Hemox 10 cm was easily implanted and removed, causing patients less discomfort during the first days after surgery. The nasal mucosa was better preserved with Merocel than with JVT. This type of material can be used in rhino-septoplasty or septoturbinoplasty.
Keywords: TURBINOPLASTY; RHINOSEPTOPLASTY; MEROCEL